1991
DOI: 10.1128/jvi.65.5.2225-2230.1991
|View full text |Cite
|
Sign up to set email alerts
|

Progressive immune dysfunction in cats experimentally infected with feline immunodeficiency virus

Abstract: Within 6 months of infection with the Petaluma isolate of feline immunodeficiency virus, specific-pathogenfree domestic cats exhibited a decrease in the percentage and number of circulating CD4+ lymphocytes and in the CD4+/CD8+ T-cell ratio, along with a marginally significant depression of pokeweed mitogen-induced lymphocyte proliferation in vitro. There was no loss of responsiveness to concanavalin A during this stage, and the cats were capable of mounting a satisfactory antibody response to a T-dependent, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(67 citation statements)
references
References 34 publications
4
62
0
1
Order By: Relevance
“…The hallmark of infection is depletion of CD4 peripheral T-cells and reduction of CD4/CD8 ratios (Ackley et al, 1990;Taniguchi et al, 1991;Torten et al, 1991;Hoffmann-Fezer et al, 1992). Decreased CD4 T-cell counts in infected cats have been reported in both natural and experimental infections (Ackley et al, 1990;Hoffmann-Fezer et al, 1992).…”
Section: Pathogenesis and Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hallmark of infection is depletion of CD4 peripheral T-cells and reduction of CD4/CD8 ratios (Ackley et al, 1990;Taniguchi et al, 1991;Torten et al, 1991;Hoffmann-Fezer et al, 1992). Decreased CD4 T-cell counts in infected cats have been reported in both natural and experimental infections (Ackley et al, 1990;Hoffmann-Fezer et al, 1992).…”
Section: Pathogenesis and Infectionmentioning
confidence: 99%
“…In addition, CD8 T-cells from FIV-infected cats produced soluble suppressor antiviral factors resembling the CD8-mediated antiviral factor (CAF) produced in HIV-positive individuals (Flynn et al, 1999;Choi et al, 2000). Infected cats possess strong T-helper activities (increased gamma interferon and IL-10 production), during early stages of FIV infection which gradually decrease with long-term infection Torten et al, 1991;Hoffmann-Fezer et al, 1992;Bendinelli et al, 1995;Liang et al, 2000). These T-cell dysfunctions and responses in FIV-infected cats closely mimic those of HIV-positive individuals (Rideout et al, 1992;Gebhard et al, 1999).…”
Section: Pathogenesis and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other immunologic abnormalities can be found in FIV-infected cats. Lymphocytes may loose the ability to proliferate in response to stimulation with mitogens or antigens, and priming of lymphocytes by immunogens may be impaired (Hara et al, 1990;Hosie and Jarrett, 1990;Taniguchi et al, 1990;Barlough et al, 1991;Taniguchi et al, 1991;Torten et al, 1991;Bishop et al, 1992a,b). Lymphocyte function may be reduced by altered expression of cell surface molecules, such as CD4, major histocompatibility complex II antigens, or cytokines and cytokine receptors (Willett et al, 1991;Ohno et al, 1992;Rideout et al, 1992;Choi et al, 2000;Mizuno et al, 2003a), or through over-expression of abnormal molecules, such as receptors (Nishimura et al, 2004), leading to disrupted cytokines production or receptor function.…”
mentioning
confidence: 99%
“…The immunosuppression caused by FIV infection manifests as a loss of response to viral antigens, a loss of response to mitogens, and the inability to launch a primary immune response against secondary pathogens [7]. Torten et al [36] observed that, together with the progression of the disease (25-44 months pi), the infected cats exhibited a reduction in their response to T-dependent immunogens but an adequate response to T-independent immunogens. In addition, these researchers observed a reduction in lymphocyte proliferation, which is induced by mitogens in the infected cats.…”
Section: Immunosuppressionmentioning
confidence: 99%